A review of propulsive mechanisms in rowing - Caplan, N.; Coppel, A.; Gardner, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
This paper reviews the fluid dynamic mechanisms that are fundamental to the rowing stroke. Complex interactions occur between the oar blade and water, and over the last 30 years our understanding of the mechanisms that govern rowing propulsion has developed significantly.